Pengaruh Implementasi Kebijakan Bantuan Operasional Keluarga Berencana Terhadap Keberhasilannya di Kota Medan - Sipahutar, Marisa; Sihombing, Tunggul; Siahaan, Asima Yanty (UIR Press, 2025)
This research aims to examine and analyze the effect of the implementation of the operational assistance for family planning policy on the success of the modern family planning program in Medan. The method used was an associative method with quantitative data analysis. Data analysis was performed using Smart PLS software version 4.1.1.5, which included validity and reliability tests for the measurement model, as well as hypothesis testing to measure the influence between policy implementation variables and programme success. The results of the research indicate that the variable implementation of the operational assistance for family planning policy affects the variable success of the modern family planning program by 0.883. This is consistent with hypothesis testing results, where the t-statistic value is 47.581, while the t-table value is 1.66, thus t-statistic > t-table (47.581 > 1.66) with a significance level of 0.000. For the independent variable, the most influential indicator is the disposition or attitude of implementers, while the least influential is human resources. For the dependent variable, the most influential indicator is the alignment of the program with its benefits, while the least influential is the alignment of the beneficiary group with the implementing organization. The coefficient of determination shows that 78% on the success of the modern family planning program is affected by the implementation of the operational assistance for family planning policy, while 22% is affected by other variables not included in this research.